Nursing in hemotherapy services: considerations on public policies associated with blood and blood components - Patrícia Aparecida Tavares Mendes; Daniela de Oliveira Matias; Maristela Moura Berlitz; Beatriz Gerbassi Costa Aguiar (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: Reflect on how the evolution of legislation related to blood and blood-based products has shaped the role of nurses in hemotherapy services. Methods: A reflective study, carried out employing surveys in databases, about the evolution of the nurse's role in hemotherapy services. Results: Several legislations, published since 1950, have encouraged blood donation and shaped the work of nurses in hemotherapy services, being the most relevant Law #10.205/2001 (Lei nº 10.205/2001), about blood collection, processing, storage, distribution, and blood transfusion; and COFEN's resolution # 629/2020 (COFEN nº 629/2020), which addresses in detail the practice of these services. Final considerations: The evolution of legislation related to blood and blood-based products contributed to the consolidation of nurses' attributions in hemotherapy services since it guaranteed legal support and defined the practices in these services.